2017
DOI: 10.3390/agronomy7010005
|View full text |Cite
|
Sign up to set email alerts
|

QTL Analysis for Drought Tolerance in Wheat: Present Status and Future Possibilities

Abstract: Abstract:In recent years, with climate change, drought stress has been witnessed in many parts of the world. In many irrigated regions also, shortage of water supply allows only limited irrigation. These conditions have an adverse effect on the productivity of many crops including cereals such as wheat. Therefore, genetics of drought/water stress tolerance in different crops has become a priority area of research. This research mainly involves use of quantitative trait locus (QTL) analysis (involving both inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
125
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(129 citation statements)
references
References 111 publications
4
125
0
Order By: Relevance
“…Quantitative trait loci associated with yield, agronomic traits and physiological traits in drought and heat stress environment underlie important genomic regions that can be considered for improvement under stress (Gupta et al., ). Earlier studies had also identified similar genomic regions for NDVI and yield contributing traits on chromosome 2A and 4B (Gao et al., ; Pinto et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative trait loci associated with yield, agronomic traits and physiological traits in drought and heat stress environment underlie important genomic regions that can be considered for improvement under stress (Gupta et al., ). Earlier studies had also identified similar genomic regions for NDVI and yield contributing traits on chromosome 2A and 4B (Gao et al., ; Pinto et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of QTLs linked to various physiological traits affecting the expression of yield had been documented for improvement of crops for stress tolerance and yield stability (Reynolds & Tuberosa, 2008). There are numerous reports on molecular markers linked with expression of QTLs at a phenotypic level for drought tolerance (Gupta et al, 2012(Gupta et al, , 2017Pinto et al, 2010), but their deployment in wheat-breeding programmes is still rare. Examples of successful use of MABB in cereals including barley, rice and maize for biotic and abiotic stress tolerance are available, but most of wheat-breeding projects in countries like Canada, USA, Australia, India and CIMMYT, Mexico are focussed on simple traits like pest resistance, disease resistance and quality traits (Gupta, Kaur, Sehgal, Sharma, & Chhuneja, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple QTL have been identified in all wheat chromosomes and results have been summarized in a meta-QTL analysis for drought and heat stress (Acuña-Galindo et al 2015) and in a recent review (Gupta et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the growth and development of wheat has been seriously influenced by drought stress, which is the significant reason restricting sustainable increase of wheat yield [20]. At present, studies on wheat response to drought stress are basically limited to phenotype, structure, physiology and biochemistry, stress-resistant genes and other studies [21], epigenetic regulation of wheat response to drought stress is rarely involved, especially the regulatory role of DNA methylation in DREB transcription factor response to drought stress. In this study, main members of DREB family in wheat were identified, the expression and promoter methylation of DREB gene were analyzed under drought stress, which would be helpful to reveal the regulatory mechanism of DNA methylation in plant response to drought stress.…”
Section: Introductionmentioning
confidence: 99%